On the use of the stepped isostress method in the prediction of creep behavior of polyamide 6 (Fracture and Structural Integrity, 2022)
The stepped isostress method (SSM) is an advanced technique which allows the prediction of the long-term behavior and enables the construction of creep master curves of materials with short-term experimental tests. However, the performance of this method is highly dependent on the numerical model and the time spent in data processing. In this paper, the effect of the extrapolation techniques on the creep curves trend is investigated using the SSM data of Polyamide test. Three extrapolation functions are used to offset the delay of the stress history: polynomial, power and exponential functions. Furthermore, a numerical routine is developed during the last step of the SSM, where the shift factors are computed taking into account the rescaling and the dwell times of each level of stresses. The processing of the SSM raw data has revealed that the rescaling parameters are the most determining factors to reach an accurate long-term creep curves. The rescaling process has shown an appropriate time, whether achieved by the exponential or power functions. Larger shift factors for exponential functions are assessed and therefore a long period of creep master curve was obtained.
Keywords: Creep; Polyamide 6; Fitting Function; SSM method; Master curve